2015
DOI: 10.1177/1356766715571389
|View full text |Cite
|
Sign up to set email alerts
|

Influence of festival attribute qualities on Slow Food tourists’ experience, satisfaction level and revisit intention

Abstract: The purpose of this study is to examine the impact of Slow Food festival attributes on visitors’ overall experience, their satisfaction level and revisit intention. A total of 209 usable questionnaires were collected from visitors at Mold Slow Food festival, and exploratory factor analysis was conducted using analysis of moment structures version 19.0. A theoretical model representing the relationships among festival attribute qualities, experience quality, satisfaction level and revisit intention is examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 46 publications
3
60
0
1
Order By: Relevance
“…Chi et al [37] discovered that respondents' satisfaction with food experiences led to overall satisfaction, which in turn affected their behavioral intentions, such as revisit intentions. Relatedly, Mason and Nassivera [38], Jung, Kim, and Yap [39], and Sohn, Lee, and Yoon [40] all suggested that visitors' satisfaction with a festival significantly influenced behavioral intention (e.g., intention to revisit the festival). Han and Hyun [29] verified that luxury hotel restaurant customers' satisfaction affected their behavioral intentions, both to re-patronize the same restaurant along with other restaurants under the same hotel.…”
Section: Behavioral Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chi et al [37] discovered that respondents' satisfaction with food experiences led to overall satisfaction, which in turn affected their behavioral intentions, such as revisit intentions. Relatedly, Mason and Nassivera [38], Jung, Kim, and Yap [39], and Sohn, Lee, and Yoon [40] all suggested that visitors' satisfaction with a festival significantly influenced behavioral intention (e.g., intention to revisit the festival). Han and Hyun [29] verified that luxury hotel restaurant customers' satisfaction affected their behavioral intentions, both to re-patronize the same restaurant along with other restaurants under the same hotel.…”
Section: Behavioral Intentionmentioning
confidence: 99%
“…Satisfaction items were adapted from previous studies [19,20,31]. Behavioral intention items were similarly prepared based on behavioral intention research [39,40,46].…”
Section: Measurementmentioning
confidence: 99%
“…Leading motivations for visiting festivals as identified in numerous studies include: socialization, entertainment, cultural exploration, family togetherness, novelty/uniqueness, excitement, escape. A small part of these however investigate festivals of local/traditional products; a recent addition is a study on a Slow Food festival, which finds festival programme, amenities and entertainment to all have impact on visitor satisfaction, while revisit intentions are mostly influenced by food and amenities (Jung, Ineson, Kim, & Yap, 2015). While most studies are focused on on-site visitor experience, a few ones examine behaviour change and level of engagement.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The business agents also showed interest in promoting slow food through specially curated restaurants and local motels for tourists. A major marketing gimmick for promoting slow food tourism can be conducted in the form of food fairs and festivals (Jung et al, 2015). Such fairs are a magnetic attraction to food-loving tourists from anywhere in the world.…”
Section: Marketing and Promotionmentioning
confidence: 99%